Agricultural incentives in Sub-Saharan Africa: policy challenges - World Bank; Townsend, Robert F (Washington, D.C. World Bank, 1999)
This study examines the state of agricultural incentives in Sub-Saharan Africa, taking stock of the current policy environment and its recent evolution.
rpm 06/02/2019
Ref
Keywords: Agricultural Economics